2011
DOI: 10.3109/0886022x.2011.623563
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy of Ginger, Arabic Gum, andBoswelliain Acute and Chronic Renal Failure

Abstract: This study was conducted to evaluate the effects of Zingiber officinale Roscoe (Ginger), Arabic gum (AG), and Boswellia on both acute and chronic renal failure (CRF) and the mechanisms underlying their effects. Acute renal failure was induced by 30 min ischemia followed by 24 h reperfusion, while CRF was induced by adenine feeding for 8 weeks. Prophylactic oral administration of ginger, AG, Boswellia, or vehicle (in control groups) was started 3 days before and along with adenine feeding in different groups or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 52 publications
4
34
0
1
Order By: Relevance
“…GA is known to have antioxidant properties, which have been illustrated in animal model of CRF [18, 31]. GA increased anti-oxidant enzymes like superoxide dismutase (SOD), catalase and glutathione [31]. GA microcapsules found to be potent anti-oxidant agent in vitro [23].…”
Section: Discussionmentioning
confidence: 99%
“…GA is known to have antioxidant properties, which have been illustrated in animal model of CRF [18, 31]. GA increased anti-oxidant enzymes like superoxide dismutase (SOD), catalase and glutathione [31]. GA microcapsules found to be potent anti-oxidant agent in vitro [23].…”
Section: Discussionmentioning
confidence: 99%
“…They have demonstrated this effect in many cell culture (Chaiyakunapruk et al, 2006;Ramkissoon et al, 2012;Kabuto et al, 2005;Mahmoud et al, 2012;AlAwwadi,2010;2013).…”
Section: Antioxidantmentioning
confidence: 99%
“…Ginger is showing anti-inflammatory effect by suppression of PG synthesis and also interference in cytokine signalling (Duke and Ayensu, 1985;Uz et al, 2009;Mahmoud et al, 2012).…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, other studies have demonstrated the reno-protective effects of ginger extract in different experimental models of renal failure [9,10].…”
Section: Introductionmentioning
confidence: 99%